Student Protagonism and Extension Curricularization: A necessary debate (Research, Society and Development, 2024)
The inclusion of extension in undergraduate curricula has been permeating debates on higher education in Brazil. This practice integrates extension activities into undergraduate curricula, promoting interaction between academia and society and leveraging student protagonism. In this context, this article seeks to discuss the role of students in the extension curricularization process at the Federal Institutes through an analysis of the PPCs of the designated courses. The research is characterized as qualitative-descriptive and was carried out through documentary analysis. Data analysis was based on Content Analysis and was carried out using ATLAS.ti software. The coded registration units were: a) extension curricularization and b) student protagonism. After analyzing the selected texts, it emerged that most of the excerpts dealt with normative aspects related to citations of existing legislation, disregarding important aspects such as the institution's conception of Extension and, especially, student participation in these activities. With regard to the proposed objective, it was observed that student participation is a topic far removed from the understanding of the practice of Extension expressed in the PPCs, and that it is necessary to advance discussions and proposals aimed at increasing student protagonism in the Extension curricularization process.